2018
DOI: 10.1111/eci.13029
|View full text |Cite
|
Sign up to set email alerts
|

Certified testosterone immunoassays for hyperandrogenaemia

Abstract: An isolated androgen measurement, even a very specific one, is unlikely to identify the hyperandrogenic milieu that characterizes patients with functional ovarian hyperandrogenism and PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Still, even when a very specific immunoassay is used, some have found that an isolated androgen measurement is unlikely to identify the hyperandrogenic mix that characterises patients with functional ovarian hyperandrogenism and PCOS [25]. Others would go further and argue that LC-MS/MS should preferably be used to identify the androgens instead [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Still, even when a very specific immunoassay is used, some have found that an isolated androgen measurement is unlikely to identify the hyperandrogenic mix that characterises patients with functional ovarian hyperandrogenism and PCOS [25]. Others would go further and argue that LC-MS/MS should preferably be used to identify the androgens instead [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Serum for sex steroid measurements was frozen at 280°C until thawed for analysis. Technical characteristics of the assays used for biochemical and hormone measurements have been described in detail elsewhere (2,4). We performed hormone assays at the same time using kits from the same production lots.…”
mentioning
confidence: 99%
“…* (above the boxes) significant differences between those PCOS phenotypes PCOM definition in our series changed the PCOS phenotype of 16.8% women but, unlike the findings of the Italian study, most of our patients were reassigned from the classic phenotype to the normoandrogenic one. This apparent discrepancy may rely on: i) we used two different immunoassays throughout the recruitment period previously compared in terms of performance for phenotyping women with PCOS [14]. Our unextracted direct RIA found hyperandrogenemia in 17.2% more women than the ICLA did.…”
Section: Discussionmentioning
confidence: 92%
“…We defined clinical hyperandrogenism as hirsutism by a modified Ferriman-Gallwey score ≥ 8. In the clinical setting, immunoassays were used to estimate biochemical hyperandrogenism using local in-house cut-offs for each assay derived from a sample of non-hyperandrogenic premenopausal female volunteers presenting with regular menses (Table 1) [13,14].…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation